A description of the likelihood ratios in the probabilistic genotyping software STRmix™. Issue 6 (24th May 2020) - Kelly, Hannah; Bright, Jo‐Anne; Coble, Michael D.; Buckleton, John S.
Abstract: Probabilistic methods of DNA profile interpretation are being adopted by forensic laboratories worldwide. One commonality to all probabilistic genotyping software is an assignment of the strength of evidence using the likelihood ratio (LR). The probabilistic genotyping software STRmix™ reports a number of LRs that differ based on the propositions considered and the level within the hierarchy of propositions considered. Within this paper, we describe the different LRs assigned in a STRmix™ software report. This article is categorized under: Forensic Biology > Interpretation of Biological Evidence Forensic Biology > Forensic DNA Technologies Abstract : STRmix™ Resolve more DNA mixtures